Hyperactive browning and hypermetabolism: potentially dangerous element in critical illness - Huang, Lu; Zhu, Lili; Zhao, Zhenxiong; Jiang, Shenglu (Frontiers in Endocrinology, 2024)
Brown/beige adipose tissue has attracted much attention in previous studies because it can improve metabolism and combat obesity through non-shivering thermogenesis. However, recent studies have also indicated that especially in critical illness, overactivated brown adipose tissue or extensive browning of white adipose tissue may bring damage to individuals mainly by exacerbating hypermetabolism. In this review, the phenomenon of fat browning in critical illness will be discussed, along with the potential harm, possible regulatory mechanism and corresponding clinical treatment options of the induction of fat browning. The current research on fat browning in critical illness will offer more comprehensive understanding of its biological characteristics, and inspire researchers to develop new complementary treatments for the hypermetabolic state that occurs in critically ill patients.